ANALISIS KEPUASAN PELANGGAN PRODUK KOSMETIK EMINA - Erina Oktaviani, (2021)
This research is a quantitative research conducted with the aim of proving and analyzing the effect of price, brand image and product quality on customer satisfaction of Emina cosmetic products. The population in this study are people who have bought or are currently using Emina cosmetics in the West Bogor District, Bogor City. The sample size used was 100 respondents, with the Non-Probability Sampling method with the type of Purposive Sampling. Data was collected by distributing questionnaires through the g-form. The data analysis technique used is the Partial Least Square (PLS) method. The results of this study indicate that the variables of price, brand image and product quality have a significant and significant effect on customer satisfaction.